Advanced fuzzy power extraction control of wind energy conversion system for power quality improvement in a grid tied hybrid generation system. Issue 5 (1st April 2016) - Bhattacharjee, Chayan; Roy, Binoy Krishna
Abstract : This paper introduces an intelligent extraction of optimum power and its dispatch by using fuzzy logic from a grid tied hybrid generation system comprising of a permanent magnet synchronous generator based wind turbine and a low concentration photovoltaic generator. For photovoltaic generator, maximum power point tracking control is implemented using fuzzy logic under varying solar irradiance. Power extracted from wind turbine is designed as a fuzzy function of the dc link voltage error, its rate of change and error in the direct axis current of the inverter. This reduces high frequency oscillations in the wind extracted power. Such an extraction is considered as a novelty of this paper. A failure mode and effect analysis is done for power converters and possible mitigation schemes are suggested for different faults. A 1:1 delta wye‐grounded transformer is used at the inverter output to eliminate the triplet harmonics. Further, dynamic performances of both fuzzy proportional‐derivative and integral (PD+I) controller and classical proportional integral (PI) controller, to control the inverter currents, are compared. The proposed method results in an enhanced power dispatch and improvement in distortions and oscillations in the converter currents. This also reduces the probability of failures in the converter switches and other passive components.